Implementasi Pengalaman Penata Anestesi Dalam Manajemen Nyeri Dengan Pemberian Analgesik Tramadol Pada Pasien Pasca Operasi Apendiktomi Di Ruang Instalasi Bedah Sentral Rs Bhayangkara Brimob Studi Phenomenology - Delviana N., Mariana; Al- Ahdad, Mufasir (NHM PRESS, 2024)
Appendicitis is inflammation of the appendix where infection occurs which causes an acute stomach. The appendix is about 6 cm to 9 cm long in adults. The base of the appendix is attached to the cecum and the point has several such as retrocecal, pelvic, antececal, preileal, retroileal, or right pericolic positions. Appendicitis according to its stage is divided into two, namely chronic and acute. Chronic appendicitis can be treated with antibiotic therapy, while acute appendicitis requires immediate surgery. Treatment of acute appendicitis is recommended with an appendectomy, namely surgical removal of the appendix, including a type of operation in the clean contamination category that allows surgical wound infections (SSI). Objective: To determine the implementation of anesthesia management in pain management by administering the analgesic Tramadol to post-appendectomy patients at Bhayangkara Brimob Hospital, Depok. Method: This research is a qualitative descriptive case study research using case analysis and cross-case analysis methods. The collection tools used in this research were interview sheets and observation sheets. The number of participants used was 4 participants. Results: The results of the study showed that the implementation applied by anesthetists in pain management was more effective using pharmacological therapy techniques, especially on a pain scale of 7-9, severe pain with the analgesic tramadol. Conclusion : The implementation of anesthesia management in pharmacological pain management using OPIOID drugs, namely tramadol, is quite effective in treating pain, both moderate pain, pain scale 4-6 and severe pain, pain scale 7-9, while in patients with cases of mild pain, the pain scale is 1- 3 can still use pharmacological therapy such as distraction and teaching deep breathing relaxation techniques